THE ARTISTIC DEPICTION OF THE CHILDREN’S WORLD IN PEARL S. BUCK’S NOVELS - Mamanabiyeva Shakhrizoda Sharofidin kizi, Yakubova Shakhrizoda Abror kizi (International Journal of Literature and Language Studies, 2026)
This article investigates the artistic depiction of the children’s world in the novels of Pearl S. Buck. The study mainly focuses on the psychological, moral, social, and emotional representation of children in Buck’s literary works. Furthermore, the article examines the writer’s narrative techniques, family themes, cultural perspectives, and humanitarian philosophy. Opinions and theories of European and American scholars are used in order to strengthen the scientific basis of the research. In addition, the article analyzes how Buck portrays children as symbols of innocence, hope, and moral continuity. The study also emphasizes the educational significance of Pearl Buck’s novels in modern literary criticism and childhood studies. The findings reveal that Buck’s literary representation of children combines realism, emotional sensitivity, and humanitarian ideals.